CRIMINAL CONVICTION OF CHILD TRAFFIC OFFENDERS REVIEWED FROM THE JUVENILE CRIMINAL JUSTICE SYSTEM - Syafi’i, Muhammad Dzikri Akbar; Pribadi, Firman Arif; Abdullah, Saiful (Faculty of Law Universitas Trunojoyo Madura, 2022)
Law Number 11 of 2012 concerning the Juvenile Criminal Justice System (hereinafter referred to as the SPPA Law) which is a formal criminal law for children specifically regulates punishment that can be imposed on children. The criminal sanctions stipulated in the SPPA Law are different from the criminal sanctions in the Criminal Code. The criminal sanctions contained in Article 71 do not include criminal sanctions of confinement and criminal sanctions of fines, nor does the SPPA Law specifically regulate criminal sanctions in lieu of imprisonment and fines. This is a problem related to children who commit criminal acts of traffic violations which in material law are threatened with imprisonment and fines. In this case, the criminal sanctions that can be imposed on children perpetrators of traffic violations are criminal sanctions contained in the SPPA Law by taking into account the principle of the best interests for children, as well as the regulations contained in the SPPA Law. The research method used in this study is a normative juridical research method, with a statute approach and a conceptual approach. The collection of sources of legal materials, both primary and secondary, is carried out through legal literature studies, recording legal documents, laws and regulations and tracing the research results of others. The results of this study show that the criminal sanctions that can be imposed on children violating traffic crimes under the SPPA Law are criminal sanctions for warning, probation, and job training.